Cognitive Predictors of Delay Discounting in Monetary Choices - Bačová, Viera; Šrol, Jakub (Studia Psychologica, 2021)
Delay discounting, the tendency to choose a smaller-sooner reward over a larger-later reward, is thought of as an expression of personality and cognitive impulsivity. In our study (N = 397), we focused on the cognitive dimension and examined the associations between monetary delay discounting tasks and various individual difference cognitive measures. A higher delay discounting was associated with performance on the tasks of general cognitive ability, cognitive reflection, scientific reasoning, and objective numeracy positively, and with self-reported intuitive thinking disposition and bias susceptibility negatively. However, of all the tasks, the overall bias susceptibility predicted delay discounting over and above all other cognitive predictors we employed. The results support the assumption about a common basis of higher monetary delay discounting and susceptibility to cognitive biases. Because of the relatively low explained variance in delay discounting by cognitive predictors, however, ample room is left for other potential personality predictors in these tasks.